Cross-Cultural Differences in Emotional Selection on Transmission of Information - Eriksson, Kimmo (Journal of cognition and culture, 2016)
Research on cultural transmission among Americans has established a bias for transmitting stories that have disgusting elements (such as exposure to rats and maggots). Conceived of as a cultural evolutionary force, this phenomenon is one type of emotional selection. In a series of online studies with Americans and Indians we investigate whether there are cultural differences in emotional selection, such that the transmission process favours different kinds of content in different countries. The first study found a bias for disgusting content (rats and maggots) among Americans but not among Indians. Four subsequent studies focused on how country interacts with kind of emotional content (disgusting vs. happy surprises and good news) in reactions to transmission of stories or information. Whereas Indian participants, compared to Americans, tended to be less interested in, and excited by, transmission of stories and news involving common disgust-elicitors (like rats), the opposite pattern held for transmission of happy surprises and good news (e.g., the opening of a new public facility). We discuss various possible explanations and implications.